2020
DOI: 10.1101/2020.02.20.956391
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Commensal oralRothia mucilaginosaproduces enterobactin – a metal chelating siderophore

Abstract: AbstractNext-generation sequencing studies of saliva and dental plaque from subjects in both healthy and diseased states have identified bacteria belonging to the Rothia genus as ubiquitous members of the oral microbiota. To gain a deeper understanding of molecular mechanisms underlying the chemical ecology of this unexplored group, we applied a genome mining approach that targets functionally important biosynthetic gene clusters (BGCs). All 45 genome… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…The two common commensal co-colonizers of the human nasopharynx, Haemophilus influenzae and Moraxella catarrhalis, do not synthesize siderophores under conditions of Fe starvation [69][70][71]. Further, although it was recently reported that Rothia mucilaginosa, a common commensal of the oral cavity, synthesizes Ent [72], it is unknown if Ent or Ent hydrolysis products are accessible to S. pneumoniae in this and other colonization sites. Based on the available information, we favor a model in which host-derived endogenous catecholamines or another bacterially derived, naturally occurring tetradentate siderophore(s), are the primary physiological substrates for PiuA.…”
Section: Discussionmentioning
confidence: 99%
“…The two common commensal co-colonizers of the human nasopharynx, Haemophilus influenzae and Moraxella catarrhalis, do not synthesize siderophores under conditions of Fe starvation [69][70][71]. Further, although it was recently reported that Rothia mucilaginosa, a common commensal of the oral cavity, synthesizes Ent [72], it is unknown if Ent or Ent hydrolysis products are accessible to S. pneumoniae in this and other colonization sites. Based on the available information, we favor a model in which host-derived endogenous catecholamines or another bacterially derived, naturally occurring tetradentate siderophore(s), are the primary physiological substrates for PiuA.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study (de Steenhuijsen Piters et al, 2016), the domination of Rothia was strongly associated with pneumonia. And iron-chelating enterobactin might explain Rothia mucilaginosa's successful oral colonization in both healthy and diseased individuals (Uranga et al, 2020). However, a recent literature showed that Rothia mucilaginosa abundance inversely correlated with sputum pro-inflammatory markers in chronic lung disease, which implies a beneficial role in the respiratory tract (Rigauts et al, 2022).…”
Section: B Amentioning
confidence: 99%
“…While there were no differences in overall aor b-diversity in sputum microbiomes among the cohorts, we identified statistically significant differences in abundance for the genera Rothia and Haemophilus, two oral microbiome community members, in the comparison of the PTB and LTBI datasets. Rothia mucilaginosa was recently reported to produce the siderophore enterobactin in the human oral niche (Uranga et al, 2020). Mtb is also a producer of siderophores (mycobactins), which are released to acquire iron from the host in infected lung tissue (De Voss et al, 2000).…”
Section: Rothia a Respiratory Tract Microbial Biomarker For Ptb?mentioning
confidence: 99%
“…Enhanced iron sequestration during an active host inflammatory response in PTB possibly diminishes the fitness and growth of Rothia species in the upper respiratory tract. This genus is a ubiquitous commensal organism of the oral cavity (Singh et al, 2019;Uranga et al, 2020). One may also speculate that the genus Haemophilus, increased in abundance in respiratory secretions of PTB compared to LTBI subjects, is due to its better adaptation to inflammatory conditions caused by the infection with Mtb.…”
Section: Rothia a Respiratory Tract Microbial Biomarker For Ptb?mentioning
confidence: 99%